A Multivariate Cointegration Analysis Of The Role Of Exports To Main Trading Partners In The Malaysian Macroeconomics - Nur Zaimah, Ubaidillah; Rossazana, Ab. Rahim (Munich University Library, 2012)
This paper investigates determinants of Malaysian export to the United States (US), Japan and Singapore using annual data from 1970 until 2010. Country specific determinants of trade include real gross domestic product, nominal effective exchange rate, inflation and inward foreign direct investment. The aim of this paper is to discern the dynamic causal chain among gross domestic product, foreign direct investment, real effective exchange rate and inflation in the context of Malaysian exports to the United States. The methodology employed applied Augmented Dickey Fuller test, Johansen and Juselius cointegration test and Vector Error Correction Model to capture the Granger-causal chain among the variables. The major findings ;(a) long-run equilibrium relationship(s) exists between Malaysian exports to its main trading partners and its macroeconomic variables, (b) Malaysia macroeconomic variables have significant influence on its exports to its main trading partners. Most specifically, real gross domestic product lead to expansion in exports performance.